DDIS-21. IN VITRO MICRODIALYSIS RECOVERY OF TRAMETINIB. (11th November 2019) - Romo, Carlos; Anders, Nicole; Scardina, Morgan; Mukherjee, Debraj; Grossman, Stuart; O Blakeley, Jaishri; Rudek-Renaut, Michelle
Abstract: BACKGROUND: Dysregulation of the mitogen-activated protein kinase and phosphoinositide 3-kinase (PI3K) pathways is common in several primary brain tumors and metastatic cancers affecting the central nervous system. Trametinib, and oral MEK1/2 inhibitor, has been effective in preclinical studies against a variety of cell lines and improves survival in select patients with gliomas. Unfortunately, limited and often short-lived benefits are frequently seen in patients. A potential explanation for this is insufficient blood brain barrier penetration at therapeutic concentrations. The primary objective of this study is to measure the in vitro relative recovery of trametinib using microdialysis to establish the feasibility of characterizing its intratumoral pharmacokinetics in vivo using this technique. METHODS: In vitro recovery experiments were performed utilizing commercially available microdialysis instruments. Two perfusion rates (0.5–1µL/min), the use of iso- and hypertonic perfusates (artificial CSF and 10% bovine serum albumin in PBS), and the addition of dimethyl sulfoxide (DMSO) were evaluated using the extraction efficiency method. Liquid chromatography-tandem mass spectrometry was used to measure the concentrations of trametinib in stock solutions, dialysate samples, and controls over time. RESULTS: Dialysate was initially collected from a solution spiked with 15ng/mL at a rate of 1µL/min for 60 minutes, the recovery was 0.3ng/mL (0.2%) in two samples and below the limit of quantification (< 0.2ng/mL) in three. Dialysate samples were then collected from a stock solution with 150ng/mL of trametinib, recovery ranged from 0.3–15.3ng/mL (0.2–10.2%) in nine detectable samples out of sixteen. Recovery was greater with the addition of DMSO to the perfusate and with the use of a hypertonic perfusate. CONCLUSIONS: The poor relative recovery of trametinib using microdialysis suggests that this technique would be unreliable in in vivo studies. Trametinib has poor aqueous solubility, limiting the ability of characterizing its pharmacokinetic profile through microdialysis.